Occupational Visibility of COVID- 19 Disaster Heroes: Analysis from the Sample of Nurse - İlknur Aydın Avci; Özen Kulakaç; Mesiya Aydın (Journal of Nursology)
Objective: The COVID-19 pandemic, which led to an urgent public health problem, is a biological disaster that had a global impact. This study aimed to examine the views of the nurses on the "superhero" discourse in the media in this disaster.Methods: The phenomenological research method, one of the qualitative research methods, was used in the study. The research was carried out between February – April 2022 with 23 nurses working in intensive care clinics.Results: In this study, the views of nurses who worked in the intensive care unit during the COVID-19 pandemic on the "superhero" discourse in the media were investigated under the themes of rise of heroism (being noticed, heroic discourse for higher efficiency, forced hero) invisibility of heroism (invisibility before the pandemic, invisibility during the pandemic) and death of heroism (the applause, I'm real… not a toy) . The findings of the study revealed that the contribution of nursing to the health system is a little more visible in crisis conditions such as pandemic.Conclusion: The visibility that emerges as "heroism" or "superheroism", the vulnerability of nurses as human beings is ignored. This “professional invisibility and heroic visibility” emerges as a paradox, and nursing either becomes “invisible” as a profession or the needs of nurses for “material and moral support” as heroes can be ignored. During crisis periods such as pandemic, the vulnerability of nurses resulting from heavy working conditions should be taken into account and nurses should be supported physically, financially and morally.